1076 Good Driving Behavior: A Reasonable Predictor Of Cpap Adherence?. (27th April 2018) - Rizzo, D; Lavigne, G; Bailes, S; Baltzan, M; Creti, L; Tran, D; Fichten, C; Libman, E
Abstract: Introduction: Obstructive Sleep Apnea (OSA) has been linked to potentially dangerous driving among fatigued individuals. When OSA is diagnosed, the usual treatment offered is continuous positive airway treatment (CPAP). Adherence to CPAP treatment remains a challenge. Here, we explore what characteristics and behaviors at time of diagnosis are associated with CPAP adherence 6 months later. Methods: Participants were 23 individuals between the ages of 25 and 70 (M=49.61), recruited from sleep clinics and were newly diagnosed with OSA by a sleep medicine specialist. At baseline, all participants completed questionnaires on driving behaviors (Driving Behaviour Questionnaire—DBQ), usual sleep experiences (Sleep Questionnaire—SQ) and general driving (General Driving Information Form—GDIF). All participants were reassessed 6 months later and self-reported CPAP treatment adherence by telephone interview. A participant was considered adherent if they reported using their treatment at least 4 hours per night, at least 80% of the time, in the 6 months preceding post-treatment testing. 14 Individuals were adherent to CPAP treatment (8 females, 6 males), and 9 individuals were non-adherent (4 females, 5 males). Results: At baseline, means comparisons showed that the Non-Adherent group reported more near-misses (GDIF item) in the previous year (M=2.375, SD=.518) than the Adherent group (M=1.643, SD=.497, p=.006). Also, the Non-Adherent group reported worse driving behaviors in general (DBQ total score) in the previous year (M=103.375, SD=29.061) than the Adherent group (M=79.077, SD=9.169, p=.050). Lastly, The Non-Adherent group reported having more difficulty concentrating (SQ item) in the previous month (M=6.438, SD=1.499) than the Adherent group (M=4.143, SD=1.875, p=.006). All other items were not statistically significant. Conclusion: This study may provide an added opportunity to identify potentially non-adherent patients in a clinical setting by inquiring them about driving experiences, with the goal of improving health and functional outcomes in all patients with OSA. The findings are preliminary to future research. Support (If Any): FRQSC, SAAQ, FRQS.